Incorporating habitats for the conservation of urban species via planning - Carswell, Jackson Alexander (Kansas State University, 2023)
The global population today is approximately 8.0 billion and is projected to increase to 9.8 billion by 2050 (United Nations n.d.). With this population growth comes a constant demand for developable land to build more housing and related infrastructure which, in turn, has heightened pressures on the natural environment. Our natural environment, including all flora and fauna, is facing the detrimental consequences of urbanization – shrinking natural habitats and ecosystem disruption. As habitats shrink, some species have adapted and become more urban, many are forced to live in constantly declining natural spaces, and others have perished. Smaller natural habitats have also resulted in more human-animal interactions and conflict. As urban communities continue to grow, they often invade the remaining natural spaces. It is important to focus on how to guide and facilitate the process of adaptation to conserve wildlife populations and retain biodiversity while at the same time keeping residents safe. Since the issue involves a myriad of disciplines and stakeholders, it is important to understand how planners can collaborate with other professionals and community members. As communities create and implement plans, urban species adaptation challenges the built environment. Consequences are the loss of habitat, dwindling food sources, encroaching noise, harmful infrastructure, and many more. Planners must aim to promote better urban animal-human co-existence. The question I, therefore, address in this report is how planners, in collaboration with other disciplines, incorporate habitats for the conservation of urban species. To answer this question, I review two plans – the Assessment of Measures to Protect Wildlife Habitat in Pasco County (the Assessment) and the State Wildlife Action Plan of 2019 (the Action Plan) from the Florida Fish and Wildlife Conservation Commission (the FWC). I selected these two plans because Florida has a diverse range of native species that these planning efforts aim to protect. Through my reviews, I examined the methods and practices used to protect core areas of habitat, while educating and encouraging professionals, different levels of government, and community members to be engaged in local environmental conservation and preservation. I also conducted semi-structured interviews where I questioned different professionals on habitat conservation and wildlife conservation measures. These interviews provided me with first-hand stories, projects precedents, and locations where methods for conservation and preservation methods have been utilized. Based on my analysis of the plans and the information gained from the interviews, I suggest methods for wildlife conservation and how these practices can be used in other localities.
Keywords: Planning; Conservation; Urban wildlife; Nature; Urbanization